(untitled) (Research, Society and Development, 2020)
The Corruption is a global problem, causing the public coffers to worsen, but it also damages social and quality aspects of the population. Analyzing this scenario, the NGO - Transparency International, since 1995, annually discloses the Corruption Perception Index (IPC), the main global indicator of corruption. In this sense, this research sought, by means of a quantitative and exploratory analysis, to verify indicators of the 12 (twelve) countries of South America: Human Development Index (HDI), GDP per in habitant, Literacy rate, Gini Index, Index Gini’s Index of Quality and Access to Health Services (QASS), life expectancy and economic freedom index and compare them with the IPC data for 2019, in order to calculate Pearson’s correlation; subsequently, the cluster analysis was performed, with the variables that showed significant correlation. For this, the following multivariate statistical techniques were used: Euclidean distance, to generate a distance matrix between countries, and the Average Hierarchical Agglomerate method to obtain the dendogram. The results indicated the formation of three groups with different characteristics in relation to corruption. Therefore, it can be said that the analyzed indicators can influence data on corruption in South America.